Substance-use disorders among child welfare and juvenile justice adolescents in residential care: The role of childhood adversities and impulsive behavior. (February 2021) - Seker, Süheyla; Habersaat, Stéphanie; Boonmann, Cyril; Palix, Julie; Jenkel, Nils; Fischer, Sophia; Fegert, Jörg M.; Kölch, Michael; Schmeck, Klaus; Schmid, Marc
Highlights: Substance-use disorders (SUDs) higher in juvenile justice than child welfare youths. Cumulative childhood adversities higher among youths with SUD in residential care. Impulsive behavior relates to SUDs among youths in residential care. Incorporating trauma-informed care may reduce SUDs among youths in residential care. Treating impulsive behavior may reduce SUDs among youths in residential care. Abstract: Background: Adolescents in the child welfare and juvenile justice systems show high rates of substance-use disorders. Yet, little is known about the association between childhood adversities and impulsive behavior involving substance-use disorders in shared residential care in the child welfare and juvenile justice systems. Objective: The aim of this study is to investigate the prevalence of substance-use disorders and their association with childhood adversities and impulsive behavior among child welfare-and juvenile justice-involved adolescents in residential care. Method: A total of 386 adolescents placed into Swiss residential care by the child welfare and juvenile justice systems (37.0% girls; age range = 10–18 years; mean age = 15.41 years) were studied. Substance-use disorders and childhood adversities were categorically assessed using the Kiddie Schedule for Affective Disorders and Schizophrenia – Present and Lifetime Version. Impulsive behavior was dimensionally measured with the Youth Psychopathic Traits Inventory. Statistical methods included descriptive analyses and logistic regression analyses. Results: Juvenile justice-involved adolescents showed higher rates of any substance-use disorder compared to child welfare-involved counterparts (38% vs. 20%; χ 2 (1) = 22.21, p < 0.001). Higher numbers of childhood adversities were found among child welfare ( U = 3039, p < 0.001) and juvenile justice ( U = 309.5, p < 0.001) youths with substance-use disorders compared to those without substance-use disorders. Impulsive behavior was related to substance-use disorders among both the child welfare ( B = 0.61, SE = 0.15, p < 0.001) and the juvenile justice groups ( B = 0.40, SE = 0.17, p = 0.02). Conclusion: Considering the high rates of substance-use disorders in both the child welfare and the juvenile justice samples, this study highlights that treating impulsive behavior and incorporating trauma-informed care for childhood adversities may reduce substance-use disorders among youths in residential care. Implications for care system practice and avenues for future research are discussed.